Large Future Increase in Exposure Risks of Extreme Heat Within Southern China Under Warming Scenario - Cao, Ning; Li, Gen; Rong, Meiyan; Yang, Jinyi; Xu, Feng (Frontiers in Earth Science, 2021)
With the continued global warming, quantifying the risks of human and social-economic exposure to extremely high temperatures is very essential. The simulated extreme high-temperature days (EHTDs) with a maximum temperature higher than 35°C (38°C, 40°C) in Southern China during 1980–1999 and 2080–2099 are analyzed using the NEX-GDDP dataset. By comparing the climatology of the two scenario periods, the multi-model ensemble mean patterns show that EHTDs will greatly increase at the end of the 21st century, and its center at 35°C is projected to shift to Guangxi from Jiangxi. Model diversities are fairly small, and the spread increases with T-level rises. EOF analysis shows that the 100-years warming will impact the southern part greater than the northern part. Trend patterns exhibit comparable results to models, but with a relatively large spread. The population and economy exposure to extremely high temperatures are calculated, showing that they both will experience a large increase in future projected decades. In historical decades, the growth of population and Gross Domestic Product have dominated the increasing exposure risks, but these effects weaken with the T-level increases. In future decades, climate change plays a leading role in affecting the exposure, and its effect strengthens with the T-level increases. For historical to future changes, the dominant contributor to population exposure changes is the climate factor (74%), while substantially 90% contribution to economy exposure changes is dominated by the combined effects of climate and economy growth.